2022
DOI: 10.1021/acssuschemeng.2c01314
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Mycelium Bio-Composite Acts as a CO2-Sink Building Material with Low Embodied Energy

Abstract: As part of the global transformation to a circular economy, modern society faces the challenge of developing sustainable building materials that do not deplete nonrenewable resources or generate environmentally destructive waste. Bio-composites based on fungal mycelium grown on agricultural waste streams have the potential to serve this purpose, reducing the ecological impact of the construction industry and the conventional materials on which it currently relies. In addition to the possible advantages in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 33 publications
(42 reference statements)
0
21
0
Order By: Relevance
“…A landmark life cycle assessment demonstrated that even a 20% displacement of ruminant meat by mycoproteins can offset its associated annual deforestation and related CO 2 emissions in half, as well as significantly lower global methane emissions from animal agriculture [ 327 ]. Fungal bio-composite materials, on the other hand, can act as a CO 2 -sink material with a negative embodied carbon (EC) value, 39.5 ​kg CO 2 eq m −3 [ 328 ]. Beyond its potential in decarbonizing the food and material industries, filamentous fungi, specifically mycorrhizal fungi that form mutualistic relationships with plants, naturally sink billions of tons of fixed atmospheric carbon annually in the underground fungal network [ 329 ].…”
Section: Future Remarks and Conclusionmentioning
confidence: 99%
“…A landmark life cycle assessment demonstrated that even a 20% displacement of ruminant meat by mycoproteins can offset its associated annual deforestation and related CO 2 emissions in half, as well as significantly lower global methane emissions from animal agriculture [ 327 ]. Fungal bio-composite materials, on the other hand, can act as a CO 2 -sink material with a negative embodied carbon (EC) value, 39.5 ​kg CO 2 eq m −3 [ 328 ]. Beyond its potential in decarbonizing the food and material industries, filamentous fungi, specifically mycorrhizal fungi that form mutualistic relationships with plants, naturally sink billions of tons of fixed atmospheric carbon annually in the underground fungal network [ 329 ].…”
Section: Future Remarks and Conclusionmentioning
confidence: 99%
“…Currently, the global mycelium market is valued at US $2.95 billion, and it is expected to reach US $5.49 billion by 2030, with a CAGR of 7.3% during a forecast period of 2022–2030 . The key driver of this growth is the sustainability of mycelium-bound biocomposites, which are not only biodegradable with a negative carbon footprint (e.g., mycelium brick ∼−39.5 kg CO 2 eq m –3 ) and renewable but also are tunable to obtain properties for specific applications. , The importance of fungi and their potential applications to humans in producing sustainable products such as phytochemicals and food cannot be overemphasized. As such, mycologya field in biology that investigates fungal sciencehas grown over the years in consideration of the untapped potential of fungi .…”
Section: Introductionmentioning
confidence: 99%
“…37,39 Mycelium-bound biocomposites are natural, low-cost, and sustainable materials with a low carbon footprint, thus contributing significantly to the circular economy and the sustainability agenda. 35 Although mycelium-bound biocomposites suffer from a lack of specification standards and challenges of comparisons of resultant properties due to the different biofabrication approaches, it is worth noting that the protocol for mycomaterial production is not complex. It utilizes low-cost materials, demands less energy (biological growth), and produces highly circular and sustainable materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indeed, a large diversity of waste-based substrates have been found to be able to grow mycelium on them, such as plants' leaves, diapers, paper, food waste, etc 7 12 , therefore promising the production of new materials without the need for depleting resources. Also, contrary to other sustainable alternatives which are plant-based, MBCs can grow on by-products which may reduce the need for land, and contrary to other sustainable alternatives based on recycling of synthetic materials, MBCs require low energy input and produces low CO 2 emission which could be further reduced by employing ambient growth conditions for the fungus 13 . MBCs can integrate into biocycles because they are biodegradable 14 – 16 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, MBCs are deemed sustainable because they are biodegradable, demand 1.5 to 6 time less energy for their fabrication as compared to other materials, can act as CO 2 -sink, and have reduced impacts on water usage, particle emissions and overall climate change 13 , 21 . Yet, their integration into a tangible biocycle is still pending.…”
Section: Introductionmentioning
confidence: 99%